Public Services in Banyuwangi Regency, East Java, Indonesia in a Just and Civilized Humanity Perspective - Hary Priyanto; Bambang Soepeno; Edy Wahyudi; Abubakar Eby Hara (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The implementation of public services must be ideal and uphold the dignity of the target community. Dissatisfaction due to the phenomenon of convoluted and slow service, reprisals by bureaucrats, siding with the interests of the applicant is known, and "underhand" payments indicate that public services in Banyuwangi Regency seem rigid, "take advantage of public needs," and do not meet the needs of the community. The phenomenon of service pathology can reduce the utilization of service facilities and trust in government performance.Bureaucrats must follow the principles of just and civilized humanity so thatplacing the community as the party served, not vice versa. Bureaucrats must guide public programs and provide clear pressure. The implementation of public services must be public oriented, not state oriented. Describe, analyze, and interpret the implementation of public services in Banyuwangi Regency according to perspectivejust and civilized humanity. Using a qualitative approach based on a constructive and participatory perspective. Primary data from interviews, secondary data from literature studies and regulations relevant to the object of research. Data analysis using the Atlas Ti 8.4.23, 2018. Public services in Banyuwangi Regency intersect with bureaucratic behavior that does not reflect the values of just and civilized humanity. Please just and civilized humanity important key in respecting the rights and obligations of the object and subject of service. Public service bureaucrats must be confident and consistent in the application of Pancasila values so that public services in Banyuwangi Regency remain effective despite experiencing an implementation deficit.